The cultural significance of traditional foods in shaping Indonesian social identity: Challenges and preservation strategies - Pugra, I Wayan; Kencanawati, Anak Agung Ayu Mirah; Kurniawan, I Gede Wahyu Antara (Yayasan Mitra Persada Nusantara, 2025)
This study explores the critical role of traditional foods in shaping the social and cultural identity of Indonesian society, with a focus on strategies for their preservation amidst modern challenges. The primary objective is to examine the interconnection between traditional foods and cultural practices, analysing their symbolic meanings and the threats posed by globalization and urbanization. Employing a document study approach, this research reviews relevant literature, journals, and historical records to understand definitions, concepts, and case studies related to traditional foods and their role in cultural identity. The analysis highlights the multifaceted roles of traditional foods in Indonesian society. Beyond serving as sustenance, these foods hold symbolic significance in rituals, ceremonies, and daily life, representing values such as unity, respect, and heritage. Specific examples include the use of tumpeng in celebrations and lemang during cultural ceremonies, which embody shared traditions and reinforce social bonds. However, modernization and shifting lifestyles have led to a decline in traditional food practices, posing a threat to their preservation. The findings underscore the urgency of preserving traditional foods as a vital component of Indonesia’s diverse cultural legacy. Strategies such as integrating traditional food education into school curricula, promoting traditional cuisines through cultural festivals, and leveraging technology to document recipes and practices are essential for safeguarding this heritage. The study concludes that preserving traditional foods requires heightened societal awareness and proactive efforts to balance modernization with cultural conservation. This research contributes to understanding traditional foods as a cornerstone of Indonesian identity and offers practical recommendations for their sustained relevance.